2020
DOI: 10.21887/ijvsbt.16.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection based Prevalence of Canine Corona Virus (CCoV) and Canine Parvo Virus (CPV) Infection in Diarrheic Dogs in South Gujarat

Abstract: The study was done on detection and prevalence of canine coronavirus (CCoV) and canine parvovirus (CPV) from the diarrhoeic dogs. Dogs presented with the diarrhoea and symptomatic illness, were tested for the CCoV and CPV infection. Diarrhoeic samples were directly processed for rapid diagnostic test using Immuno-chromatography based lateral flow assay test (LFA). It is a fast, rapid and specific for the CCoV and CPV detection. Out of total 109 samples processed by the LFA, 05 (4.58 %) were found positive for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…The less severe form of rabies, known as "paralytic/dumb rabies," results in death because of muscular paralysis. As it is deadliest disease of household pet, it must require 'One health' approach to prevent the disease (Desai et al, 2018 a ) [8] Worldwide occurrences of rabies deaths can be avoided through public awareness campaigns (Desai et al, 2018 b ) [9] , dog vaccinations, and the proper preand post-bite care procedures advised by the WHO. Quick wound cleaning with soap and running water can significantly lower the viral load and limit the risk of rabies infection in the future.…”
Section: Rabiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The less severe form of rabies, known as "paralytic/dumb rabies," results in death because of muscular paralysis. As it is deadliest disease of household pet, it must require 'One health' approach to prevent the disease (Desai et al, 2018 a ) [8] Worldwide occurrences of rabies deaths can be avoided through public awareness campaigns (Desai et al, 2018 b ) [9] , dog vaccinations, and the proper preand post-bite care procedures advised by the WHO. Quick wound cleaning with soap and running water can significantly lower the viral load and limit the risk of rabies infection in the future.…”
Section: Rabiesmentioning
confidence: 99%
“…Canine Parvoviral gastroenteritis: Canine parvovirus enteritis (PVE), which is caused by three varieties of canine parvovirus type 2 (CPV-2; family Parvoviridae, Genus Parvovirus), is the major cause of morbidity and mortality worldwide in dogs (Desai et al, 2020 a ; Desai et al, 2020 b ) [8,9] . In the mid-to-late 1970s, CPV-2 arose as a cause of acute canine enteritis, presumably from another carnivore parvovirus (cats or other hosts), spreading swiftly and causing global outbreaks.…”
Section: Rabiesmentioning
confidence: 99%
See 2 more Smart Citations
“…When an outbreak has been confirmed, the calves that have been clinically afflicted are the primary carriers of the virus. According to Desai et al (2020a) [3] , Desai et al (2020b) [4] , Desai et al 2021 [5] , Joshi et al (2022a) [10] , and Joshi et al (2022b) [11] , animal coronavirus can be swiftly identified by using the quick, low-cost, and practical rapid lateral flow assay test. Two of the most significant problems associated with bovine sickness are the development of antibiotic resistance and the presence of antibiotic residue in cow's milk (Patel et al, 2019 andPatel et al, 2020) [21,20] .…”
Section: Introductionmentioning
confidence: 99%